1949
DOI: 10.1021/ja01169a502
|View full text |Cite
|
Sign up to set email alerts
|

The Cryoscopic Behavior of 1,1-Dimethylcyclohexane Containing Certain Hydrocarbon Impurities

Abstract: NOTES 361Since the dispersion of both the refractivity and impurities. This study was prompted by the the Verdet constant is governed by the term observation that introduction of a small amount of ZAi/(vi2 -v2), constancy of the ratio A V / A n cis-1,2-dimethylcyclohexane as an impurity in 1,lwould be indicative of the fact that the electronic dimethylcyclohexane caused an increase in the transitions responsible for both are identical. The freezing point of the latter hydrocarbon, instead data in the last colu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1950
1950
1952
1952

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Evans et al (29) reported irregularities involving increases in freezing point instead of decreases upon introduction of small amounts of one hydrocarbon into another, due to solid solution effect. Some solutes produced only a fraction of the normal lowering.…”
Section: Miscellaneousmentioning
confidence: 99%
“…Evans et al (29) reported irregularities involving increases in freezing point instead of decreases upon introduction of small amounts of one hydrocarbon into another, due to solid solution effect. Some solutes produced only a fraction of the normal lowering.…”
Section: Miscellaneousmentioning
confidence: 99%